Fiber-reinforced composites : - Mallick, P. K. (CRC Press, 2008)
Clarifies the differences in the characteristics and behavior of fiber-reinforced polymers and common structural metals and presents fundamental design considerations and useful equations. Contains tables, illustrations, bibliographies, and listings of available computer programs, journals, societies, and other information for practicing engineers. Includes worked-out examples and problems for students.